Prediction of aluminium concentration in molten zinc pot of continuous hot dip galvanising line - Shim, JH; Chung, SH; Cho, YW (TAYLOR & FRANCIS LTD, 2002)
The strict control of aluminium concentration in a galvanising pot is extremely important to meet the high surface quality of galvanised steels that has been demanded by the industry. The present study proposes a mathematical model for the prediction of aluminium concentration in a galvanising pot of a continuous hot dip galvanising line. It is assumed that aluminium in the molten zinc pot is consumed as coating layer, dross, and inhibition layer. The quantities of aluminium consumed as dross and inhibition layer in the molten zinc pot are evaluated using the results of physical model experiments available in the literature. The operation conditions of the continuous hot dip galvanising line are online collected and then used as input data for the model. It is found that dross is a main source of the preferential consumption of aluminium in the molten zinc pot. The predicted pot aluminium concentration follows the trend of experimentally measured values rather well during both galvanising and galvannealing operations.